Tensile new energy charging pile cable
By using modified hydroxyapatite and other components in the sheath layer of the new energy charging pile cable, the problem of insufficient tensile resistance and corrosion resistance of the sheath layer is solved, which significantly improves the tensile resistance and corrosion resistance of the cable and extends its service life.
Patent Information
- Application Number
- CN202411955888.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-28
- Publication Date
- 2025-03-21
AI Technical Summary
The sheathing layer of the new energy charging pile cable has poor tensile resistance and corrosion resistance, and cannot effectively withstand heavy load tension, resulting in faster cable damage and shorter service life.
The hydroxyapatite is modified by the maleic acid-acrylic acid copolymer sodium salt to form a dense and stable sheath layer.
It significantly improves the tensile resistance and corrosion resistance of the cable sheath layer of the new energy charging pile, extends the service life of the cable, and enhances its ability to withstand load tension.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of cables, and in particular to a tensile-resistant new energy charging pile cable. Background Art
[0002] New energy charging pile cable, also known as electric vehicle charging cable or charging pile cable, is a key connecting component for power transmission between electric vehicle charging devices and charging infrastructure. It is equipped with a variety of lines including signal lines, control lines, power auxiliary lines, etc. to ensure precise control of the charging process and safety of operation. This cable usually has high conductivity and good flexibility, and is suitable for charging stations, parking lots, hotels, communities, garages and other places In daily use, new energy charging pile cables will frequently experience external forces such as plugging, unplugging, and moving. These external forces first act on the sheath layer of the cable. If the sheath layer has poor tensile strength, once it is subjected to a large degree of tensile force, it may cause the sheath layer to break, which in turn affects the insulation layer and conductor inside the cable. Once the conductor breaks, the charging current cannot be transmitted normally, the charging process will be interrupted, and the vehicle will not be able to charge normally. However, although the sheath layer of the current new energy charging pile cable has certain tensile strength, its performance is limited and cannot withstand significant load tension. Frequent load tension acting on the sheath layer with poor tensile strength will also accelerate the decline in the corrosion resistance of the sheath layer, thereby accelerating the damage rate of the cable and shortening its service life.
[0003] Therefore, improving the tensile strength and corrosion resistance of the cable sheath layer of new energy charging piles is a technical problem that needs to be solved urgently. Summary of the invention
[0004] The present invention proposes a tensile-resistant new energy charging pile cable, which solves the problem of poor tensile resistance and poor corrosion resistance of the sheath layer of the new energy charging pile cable in the related art.
[0005] The technical solution of the present invention is as follows: The present invention provides a tensile-resistant new energy charging pile cable, comprising a conductor, an insulating layer, a shielding layer and a sheath layer arranged in sequence from the inside to the outside, wherein the sheath layer comprises the following components in parts by weight: 60-70 parts of chlorinated polyethylene, 15-20 parts of polyisoprene, 5-10 parts of ethylene-methyl methacrylate copolymer, 8-18 parts of acrylonitrile-butadiene-styrene copolymer, 20-30 parts of modified hydroxyapatite, 1-5 parts of lubricant, 3-6 parts of plasticizer, 30-40 parts of flame retardant, and 1-3 parts of antioxidant; The raw materials of the modified hydroxyapatite include hydroxyapatite and a modifier; The modifier includes maleic acid-acrylic acid copolymer sodium salt; The weight ratio of the hydroxyapatite to the modifier is 45:1-7.
[0006] As a further technical solution, the weight ratio of the hydroxyapatite to the modifier is 15:1-2.
[0007] When the weight ratio of hydroxyapatite and modifier is 15:1~2, the tensile resistance and corrosion resistance of the sheath layer of the new energy charging pile cable can be further improved.
[0008] As a further technical solution, the preparation method of the modified hydroxyapatite comprises the following steps: dissolving the sodium salt of maleic acid-acrylic acid copolymer in water, adding the hydroxyapatite, dispersing evenly, and drying to obtain the modified hydroxyapatite.
[0009] As a further technical solution, the weight average molecular weight of the maleic acid-acrylic acid copolymer sodium salt is 20,000-30,000.
[0010] As a further technical solution, the modifier further includes stannate, and the weight ratio of the stannate to the sodium salt of the maleic acid-acrylic acid copolymer is 1:2-5.
[0011] When the modifier also includes stannate, the surface modification of hydroxyapatite by sodium salt of maleic acid-acrylic acid copolymer and stannate can further improve the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable. The reason may be that after the stannate and hydroxyapatite react, they can better combine with sodium salt of maleic acid-acrylic acid copolymer, thereby improving the modification effect of sodium salt of maleic acid-acrylic acid copolymer on hydroxyapatite, and a more stable and dense sheath layer can be prepared, thereby further improving the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable. By adjusting the weight ratio of stannate and sodium salt of maleic acid-acrylic acid copolymer, when the weight ratio of stannate and sodium salt of maleic acid-acrylic acid copolymer is 1:2~5, the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable can be further improved.
[0012] As a further technical solution, the preparation method of the modified hydroxyapatite comprises the following steps: A1. After dispersing the hydroxyapatite in a polyvinyl alcohol aqueous solution, adding the stannate, mixing, drying, calcining, and crushing to obtain a mixture; A2. Dissolving the sodium salt of maleic acid-acrylic acid copolymer in water, adding the mixture, dispersing evenly, and drying to obtain the modified hydroxyapatite.
[0013] As a further technical solution, the weight ratio of the hydroxyapatite to the polyvinyl alcohol aqueous solution is 1:1~1.2.
[0014] As a further technical solution, in step A1, the mass fraction of the polyvinyl alcohol aqueous solution is 10% to 15%; during the calcination, the temperature is 700 to 800° C. and the time is 2 to 3 hours.
[0015] As a further technical solution, the stannate includes one or more of zinc hydroxystannate, calcium stannate, and zinc stannate.
[0016] As a further technical solution, when the stannate includes zinc hydroxystannate and calcium stannate, the weight ratio of the zinc hydroxystannate to the calcium stannate is 3:1.
[0017] As a further technical solution, the lubricant is one or more of calcium stearate, sodium stearate, and molybdenum disulfide.
[0018] As a further technical solution, the plasticizer is one or more of trioctyl trimellitate, dioctyl phthalate, and diisononyl phthalate.
[0019] As a further technical solution, the flame retardant is one or more of triisopropylphenyl phosphate, magnesium hydroxide, and aluminum hydroxide.
[0020] As a further technical solution, the antioxidant is one or both of antioxidant 1010 and antioxidant B215.
[0021] As a further technical solution, the conductor is made of pure copper or copper alloy; the insulating layer is an EPDM rubber insulating layer; and the shielding layer is a copper wire braided shielding layer.
[0022] The present invention also proposes a method for preparing a stretch-resistant new energy charging pile cable, comprising the following steps: S1, extruding the insulating layer onto the outer layer of the conductor to obtain a conductor coated with the insulating layer; S2, winding a shielding layer around the outer side of the conductor coated with the insulating layer to obtain a semi-finished cable; S3. After the components of the sheath layer are evenly mixed, they are kneaded and extruded on the outside of the semi-finished cable to obtain the new energy charging pile cable.
[0023] As a further technical solution, in step S3, during the banburying, the temperature is 80-85° C. and the time is 4-5 min.
[0024] The working principle and beneficial effects of the present invention are: In the present invention, the sheath layer of the new energy charging pile cable is based on chlorinated polyethylene, combined with polyisoprene, ethylene-methyl methacrylate copolymer, acrylonitrile-butadiene-styrene copolymer, modified hydroxyapatite and other additives, and the prepared sheath layer has good tensile strength and corrosion resistance. Among them, the modifier in the modified hydroxyapatite includes sodium salt of maleic acid-acrylic acid copolymer. The use of sodium salt of maleic acid-acrylic acid copolymer to modify hydroxyapatite can promote the uniform dispersion of hydroxyapatite in the organic matrix system, thereby improving the degree of bonding between hydroxyapatite and the remaining components in the sheath layer, thereby forming a dense and stable internal structure of the sheath layer, and improving the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable. DETAILED DESCRIPTION
[0025] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the following embodiments and comparative examples, the model of chlorinated polyethylene is CPE135; the model of polyisoprene is IR70; the model of ethylene-methyl methacrylate copolymer is WH303-F; the model of acrylonitrile-butadiene-styrene copolymer is CF-610A; the particle size of hydroxyapatite is 30 μm, and the model is HAP08-Y; the model of sodium salt of maleic acid-acrylic acid copolymer is PMAS-90, and the weight average molecular weight is 20,000; the model of ethylene propylene diene monomer rubber is EPDM 4570.
[0027] Example 1 A tensile-resistant new energy charging pile cable comprises a conductor, an insulating layer, a shielding layer and a sheath layer arranged in sequence from the inside to the outside, wherein the sheath layer comprises the following components in parts by weight: 60 parts of chlorinated polyethylene, 15 parts of polyisoprene, 5 parts of ethylene-methyl methacrylate copolymer, 8 parts of acrylonitrile-butadiene-styrene copolymer, 20 parts of modified hydroxyapatite, 1 part of calcium stearate, 3 parts of trioctyl trimellitate, 30 parts of magnesium hydroxide, 1 part of antioxidant 1010; The raw materials of modified hydroxyapatite include hydroxyapatite and a modifier in a weight ratio of 45:1; The modifier includes maleic acid-acrylic acid copolymer sodium salt; The preparation method of modified hydroxyapatite comprises the following steps: dissolving 1 part of sodium salt of maleic acid-acrylic acid copolymer in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite; A method for preparing a stretch-resistant new energy charging pile cable comprises the following steps: S1, extruding an EPDM rubber insulation layer onto an outer layer of a pure copper conductor to obtain a conductor coated with an insulation layer; S2, winding a copper wire braided shielding layer around the outer side of the conductor covered with the insulating layer to obtain a semi-finished cable; S3. After the components of the sheath layer are evenly mixed, they are kneaded at 80°C for 5 minutes and extruded on the outside of the semi-finished cable to obtain a new energy charging pile cable.
[0028] Example 2 A tensile-resistant new energy charging pile cable comprises a conductor, an insulating layer, a shielding layer and a sheath layer arranged in sequence from the inside to the outside, wherein the sheath layer comprises the following components in parts by weight: 65 parts of chlorinated polyethylene, 18 parts of polyisoprene, 8 parts of ethylene-methyl methacrylate copolymer, 13 parts of acrylonitrile-butadiene-styrene copolymer, 25 parts of modified hydroxyapatite, 3 parts of sodium stearate, 5 parts of dioctyl phthalate, 35 parts of aluminum hydroxide, 2 parts of antioxidant B215; The raw materials of modified hydroxyapatite include hydroxyapatite and a modifier in a weight ratio of 45:1; The modifier includes maleic acid-acrylic acid copolymer sodium salt; The preparation method of modified hydroxyapatite comprises the following steps: dissolving 1 part of sodium salt of maleic acid-acrylic acid copolymer in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite; A method for preparing a stretch-resistant new energy charging pile cable comprises the following steps: S1, extruding an EPDM rubber insulation layer onto an outer layer of a pure copper conductor to obtain a conductor coated with an insulation layer; S2, winding a copper wire braided shielding layer around the outer side of the conductor covered with the insulating layer to obtain a semi-finished cable; S3. After the components of the sheath layer are evenly mixed, they are kneaded at 82°C for 4.5 minutes and extruded on the outside of the semi-finished cable to obtain a new energy charging pile cable.
[0029] Example 3 A tensile-resistant new energy charging pile cable comprises a conductor, an insulating layer, a shielding layer and a sheath layer arranged in sequence from the inside to the outside, wherein the sheath layer comprises the following components in parts by weight: 70 parts of chlorinated polyethylene, 20 parts of polyisoprene, 10 parts of ethylene-methyl methacrylate copolymer, 18 parts of acrylonitrile-butadiene-styrene copolymer, 30 parts of modified hydroxyapatite, 5 parts of sodium stearate, 6 parts of dioctyl phthalate, 40 parts of aluminum hydroxide, 3 parts of antioxidant B215; The raw materials of modified hydroxyapatite include hydroxyapatite and a modifier in a weight ratio of 45:7; The modifier includes maleic acid-acrylic acid copolymer sodium salt; The preparation method of modified hydroxyapatite comprises the following steps: dissolving 7 parts of sodium salt of maleic acid-acrylic acid copolymer in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite; A method for preparing a stretch-resistant new energy charging pile cable comprises the following steps: S1, extruding an EPDM rubber insulation layer onto an outer layer of a pure copper conductor to obtain a conductor coated with an insulation layer; S2, winding a copper wire braided shielding layer around the outer side of the conductor covered with the insulating layer to obtain a semi-finished cable; S3. After the components of the sheath layer are evenly mixed, they are kneaded at 85°C for 4 minutes and extruded on the outside of the semi-finished cable to obtain a new energy charging pile cable.
[0030] Example 4 The only difference between this embodiment and embodiment 2 is that in this embodiment, the preparation method of modified hydroxyapatite includes the following steps: after dissolving 7 parts of sodium salt of maleic acid-acrylic acid copolymer in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite.
[0031] Example 5 The only difference between this embodiment and embodiment 2 is that in this embodiment, the preparation method of modified hydroxyapatite includes the following steps: after dissolving 3 parts of sodium salt of maleic acid-acrylic acid copolymer in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite.
[0032] Example 6 The only difference between this embodiment and embodiment 2 is that in this embodiment, the preparation method of modified hydroxyapatite includes the following steps: after dissolving 6 parts of maleic acid-acrylic acid copolymer sodium salt in 55 parts of water, adding 45 parts of hydroxyapatite, dispersing evenly, and drying to obtain modified hydroxyapatite.
[0033] Example 7 The only difference between this embodiment and embodiment 2 is that in this embodiment, the preparation method of modified hydroxyapatite includes the following steps: after dispersing 45 parts of hydroxyapatite in 45 parts of 10% by mass polyvinyl alcohol aqueous solution, adding 6 parts of stannate, mixing, drying, calcining at 750°C for 2.5h, and crushing to obtain modified hydroxyapatite; the stannate is composed of zinc hydroxystannate and calcium stannate in a weight ratio of 3:1.
[0034] Example 8 The only difference between this embodiment and embodiment 6 is that in this embodiment, the preparation method of modified hydroxyapatite includes the following steps: A1. After dispersing 45 parts of hydroxyapatite in 54 parts of a 10% by mass aqueous solution of polyvinyl alcohol, 3 parts of stannate were added, mixed, dried, calcined at 750° C. for 2.5 h, and crushed to obtain a mixture; the stannate consisted of zinc hydroxystannate and calcium stannate in a weight ratio of 3:1; A2. Dissolve 3 parts of sodium salt of maleic acid-acrylic acid copolymer in 50 parts of water, add the mixture, disperse evenly, and dry to obtain modified hydroxyapatite.
[0035] Example 9 The only difference between this embodiment and embodiment 8 is that in this embodiment, 0.5 parts of stannate and 5.5 parts of sodium salt of maleic acid-acrylic acid copolymer are added.
[0036] Example 10 The only difference between this embodiment and embodiment 8 is that in this embodiment, 2 parts of stannate are added and 4 parts of sodium salt of maleic acid-acrylic acid copolymer are added.
[0037] Embodiment 11 The only difference between this embodiment and embodiment 8 is that in this embodiment, 1 part of stannate is added and 5 parts of sodium salt of maleic acid-acrylic acid copolymer is added.
[0038] Comparative Example 1 The only difference between this comparative example and Example 1 is that in this comparative example, the modified hydroxyapatite is replaced by an equal amount of hydroxyapatite.
[0039] Comparative Example 2 The only difference between this comparative example and Example 1 is that in this comparative example, 20 parts of modified hydroxyapatite are replaced by an equal amount of hydroxyapatite and sodium salt of maleic acid-acrylic acid copolymer in a weight ratio of 45:1.
[0040] The new energy charging pile cables prepared in Examples 1 to 11 and Comparative Examples 1 to 2 were subjected to the following performance tests: ① Tensile performance test: Take a sheath layer sample from the sheath layer of the new energy charging pile cable, and test its tensile strength and elongation at break according to the method of GB / T1040.1-2018 "Determination of tensile properties of plastics Part 1: General Principles". The test speed is 100mm / min, and the test result is the average value of 5 samples; ② Corrosion resistance test: After the above-mentioned sheath layer samples are immersed in a hydrochloric acid solution with a mass fraction of 18% for 35 days, the tensile strength of the immersed sheath layer samples is tested according to the above-mentioned tensile strength test method, and the tensile strength change rate is calculated according to the following formula: tensile strength change rate (%) = (tensile strength after corrosion - tensile strength before corrosion) / tensile strength before corrosion × 100%. The test result is the average value of 5 samples, and the test result is retained to 2 decimal places.
[0041] The test results are shown in Table 1 below: Table 1 Sheath layer performance test results of Examples 1 to 11 and Comparative Examples 1 to 2
[0042] Compared with comparative examples 1 to 2, the tensile strength and elongation at break of Example 1 are significantly improved. After the corrosion resistance test, the change rate of the tensile strength is significantly reduced, indicating that the modifier in the modified hydroxyapatite is maleic acid-acrylic acid copolymer sodium salt. Modification of hydroxyapatite with maleic acid-acrylic acid copolymer sodium salt can improve the tensile strength and corrosion resistance of the new energy charging pile cable sheath layer.
[0043] Compared with Examples 2 and 4, the tensile strength and elongation at break of Examples 5 to 6 are improved, and after the corrosion resistance test, the change rate of the tensile strength is reduced, indicating that when the weight ratio of hydroxyapatite and modifier is 15:1 to 2, the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable can be further improved.
[0044] Compared with Examples 6 to 7, the tensile strength and elongation at break of Examples 8 to 11 are improved, and after the corrosion resistance test, the change rate of the tensile strength is reduced, indicating that when the modifier also includes stannate, the surface modification of hydroxyapatite using sodium salt of maleic acid-acrylic acid copolymer and stannate can further improve the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable.
[0045] Compared with Examples 8 to 9, the tensile strength and elongation at break of Examples 10 to 11 are improved, and after the corrosion resistance test, the change rate of tensile strength is reduced, indicating that when the weight ratio of stannate and sodium salt of maleic acid-acrylic acid copolymer is 1:2 to 5, the tensile strength and corrosion resistance of the sheath layer of the new energy charging pile cable can be further improved.
[0046] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A tensile-resistant new energy charging pile cable, comprising a conductor, an insulating layer, a shielding layer and a sheath layer arranged in sequence from the inside to the outside, characterized in that: The sheath layer comprises the following components in parts by weight: 60-70 parts of chlorinated polyethylene, 15-20 parts of polyisoprene, 5-10 parts of ethylene-methyl methacrylate copolymer, 8-18 parts of acrylonitrile-butadiene-styrene copolymer, 20-30 parts of modified hydroxyapatite, 1-5 parts of lubricant, 3-6 parts of plasticizer, 30-40 parts of flame retardant, and 1-3 parts of antioxidant; The raw materials of the modified hydroxyapatite include hydroxyapatite and a modifier; The modifier includes maleic acid-acrylic acid copolymer sodium salt; The weight ratio of the hydroxyapatite to the modifier is 45:1-7.
2. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The weight ratio of the hydroxyapatite to the modifier is 15:1-2.
3. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The preparation method of the modified hydroxyapatite comprises the following steps: dissolving the sodium salt of maleic acid-acrylic acid copolymer in water, adding the hydroxyapatite, dispersing evenly, and drying to obtain the modified hydroxyapatite.
4. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The weight average molecular weight of the maleic acid-acrylic acid copolymer sodium salt is 20,000-30,000.
5. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The modifier further comprises stannate, and the weight ratio of the stannate to the sodium salt of maleic acid-acrylic acid copolymer is 1:2-5.
6. The stretch-resistant new energy charging pile cable according to claim 5, characterized in that: The preparation method of the modified hydroxyapatite comprises the following steps: A1. After dispersing the hydroxyapatite in a polyvinyl alcohol aqueous solution, adding the stannate, mixing, drying, calcining, and crushing to obtain a mixture; A2. Dissolving the sodium salt of maleic acid-acrylic acid copolymer in water, adding the mixture, dispersing evenly, and drying to obtain the modified hydroxyapatite.
7. The stretch-resistant new energy charging pile cable according to claim 6, characterized in that: The weight ratio of the hydroxyapatite to the polyvinyl alcohol aqueous solution is 1:1-1.2; In step A1, the mass fraction of the polyvinyl alcohol aqueous solution is 10% to 15%; during the calcination, the temperature is 700 to 800° C. and the time is 2 to 3 hours.
8. The stretch-resistant new energy charging pile cable according to claim 5, characterized in that: The stannate includes one or more of hydroxy zinc stannate, calcium stannate, and zinc stannate; when the stannate includes hydroxy zinc stannate and calcium stannate, the weight ratio of the hydroxy zinc stannate to the calcium stannate is 3:
1.
9. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The lubricant is one or more of calcium stearate, sodium stearate, and molybdenum disulfide; and / or The plasticizer is one or more of trioctyl trimellitate, dioctyl phthalate, and diisononyl phthalate; and / or The flame retardant is one or more of triisopropylphenyl phosphate, magnesium hydroxide, and aluminum hydroxide; and / or The antioxidant is one or both of antioxidant 1010 and antioxidant B215.
10. The stretch-resistant new energy charging pile cable according to claim 1, characterized in that: The conductor is made of pure copper or copper alloy; the insulating layer is an EPDM rubber insulating layer; and the shielding layer is a copper wire braided shielding layer.
Citation Information
Cited By
High-wear-resistance anti-bending power cable and preparation method thereof
CN120356726A
A highly wear-resistant and bending-resistant power cable and its preparation method
CN120356726B
Flame-retardant composite material for safety helmet and preparation method of flame-retardant composite material
CN121249091A